MATERNAL KNOWLEDGE OF PRACTICES THAT CAUSE DIARRHOEA AND DIARRHOEAL DISEASE PREVENTION - IDUORIYEKEMWEN N.J; OSAROGIAGBON O. WILSON (Ntec Specialist, 2011)
Background: Despite the remarkable reduction in global diarrhoeal disease (DD) mortality, it still remains the second major cause of childhood illness especially in developing countries. Prevention is key to sustained reduction of the disease burden, thus information which caregiver possess is vital. Objective: The aim of this study is to ascertain maternal knowledge of practices that cause diarrhoea and diarrhoea prevention measures in order to assess current health knowledge of mothers. Method: Mothers, whose children had diarrhea presenting in the Children's Emergency rooms or in-patient wards of the Stella Obasanjo Hospital and University of Benin Teaching Hospital, Benin city, were interviewed using a pretested semi-structured questionnaire designed for the study. Result: a total of 104 mothers aged 15 to 41 years participated in the study. Majority were young mothers age ≤ 30 years, who had secondary level of education and were in the lower social class. Only 27(26%) of the mothers' had correct knowledge of the definition of diarrhoea. Majority 78(75.0%) of the mothers' had limited knowledge on the practice that cause diarrhoea. Also majority 65(62.5%) of the mothers in the study did not know that diarrhoea could be prevented. Of the few mothers that knew that diarrhoea could be prevented only 6(15.4%) had good knowledge of diarrhoea prevention. Majority 77(74.7%) of mothers also admitted that they had no formal health education on diarrhea. Conclusion: This study reveals that the present generations of mothers are not sufficiently health educated on the issues of diarrhoea as mothers were 20years ago during the ORT campaign era. Thus emphasizing the need for intensive health education of mothers on diarrhoea and its prevention.